2019
DOI: 10.1515/cclm-2019-0202
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new rapid method for the determination of adalimumab serum levels with two established ELISA kits

Abstract: Background Therapeutic drug monitoring (TDM) of adalimumab (ADA) in inflammatory bowel diseases (IBDs) has gained increased attention since several studies showed a correlation between drug levels and mucosal healing. The limitations of routine usage of enzyme-linked immunoabsorbent assay (ELISA) kits for measuring serum ADA concentrations have prompted the development of rapid methods, such as Quantum Blue (QB). We evaluated the interchangeability and agreement between the QB method and two established ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In studies where these ELISA formats were compared, a good correlation between them was shown (correlation coefficients >0.9). 26 27 29 40 41 Other assay formats also correlated well with ELISA. In four studies, ELISA was compared with homogenous mobility shift assay (HMSA).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In studies where these ELISA formats were compared, a good correlation between them was shown (correlation coefficients >0.9). 26 27 29 40 41 Other assay formats also correlated well with ELISA. In four studies, ELISA was compared with homogenous mobility shift assay (HMSA).…”
Section: Resultsmentioning
confidence: 81%
“…Several assay formats are available to measure biopharmaceutical blood concentrations, of which ELISA is the most widely used. In total, 20 studies were identified that compared two or more formats for biopharmaceutical blood concentration measurement 23–42. In 12 studies, agreement between different assay formats and ELISA formats was investigated 23–27 29 34 36 37 40–42.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the infliximab case, despite an excellent correlation of infliximab levels between assays, a substantial variation in some results and systematic biases of infliximab trough levels was noted which could result in divergent therapeutic decisions for some patients (83). Similarly, in the comparative study measuring adalimumab levels in patient sera, a lack of interchangeability between methods was observed, with greater differences noted as ADA levels increased (84). This disagreement in results, evident also in other studies, has led to calls from several groups for the need for standardization of assays for detection of levels of anti-TNFs and ADA in clinical samples (32,33,73).…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care assays for detecting IFX levels, adalimumab levels, and anti-IFX antibodies are commercially available. However, they are limited by their ability to use serum instead of blood (58)(59)(60). As with other point-of-care tests, there are concerns around quality control, reliability, cost, and external validation.…”
Section: Point-of-care Testingmentioning
confidence: 99%